2018
DOI: 10.1128/mbio.02309-17
|View full text |Cite
|
Sign up to set email alerts
|

Glycan-Glycan Interaction Determines Shigella Tropism toward Human T Lymphocytes

Abstract: Direct interactions between bacterial and host glycans have been recently reported to be involved in the binding of pathogenic bacteria to host cells. In the case of Shigella, the Gram-negative enteroinvasive bacterium responsible for acute rectocolitis, such interactions contribute to bacterial adherence to epithelial cells. However, the role of glycans in the tropism of Shigella for immune cells whose glycosylation pattern varies depending on their activation state is unknown. We previously reported that Shi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 30 publications
3
25
0
Order By: Relevance
“…Human and bovine milk contain LacCer as a major GSL component , indicating that milk‐derived LacCer is a putative trap and blocking pathogen binding in the intestines, and that milk‐derived LacCer protects the host from invading pathogens. Interactions between the sugar moieties of gangliosides and the polysaccharide moieties of Shigella LPS were found to facilitate binding of bacteria to human CD4 + T cells . Taken together, these observations suggest that specific carbohydrate‐carbohydrate interactions between sugar moieties of GSL and of pathogen‐associated molecular pattern (PAMP) may be related to various immune disorders.…”
Section: Gsls As Immune Modulatorsmentioning
confidence: 87%
“…Human and bovine milk contain LacCer as a major GSL component , indicating that milk‐derived LacCer is a putative trap and blocking pathogen binding in the intestines, and that milk‐derived LacCer protects the host from invading pathogens. Interactions between the sugar moieties of gangliosides and the polysaccharide moieties of Shigella LPS were found to facilitate binding of bacteria to human CD4 + T cells . Taken together, these observations suggest that specific carbohydrate‐carbohydrate interactions between sugar moieties of GSL and of pathogen‐associated molecular pattern (PAMP) may be related to various immune disorders.…”
Section: Gsls As Immune Modulatorsmentioning
confidence: 87%
“…Although the role of the lipid A, core, and O antigen moieties in these processes have been extensively studied, a comprehensive understanding of the interplay between LPS and pathogenesis will require further research. For instance, interactions of LPS with host proteins has been the focus of many studies, but recent research suggests that glycan-glycan interactions between bacteria and their hosts may be more relevant than previously realized [194][195][196]. The advent of new glycan arrays could facilitate the screening and discovery of novel LPS interactions and yield new insights into pathogenic processes [194,197,198].…”
Section: Discussionmentioning
confidence: 99%
“…A later study by O’Riordan et al showed that glycans from several bacterial pathogens are able to interact with the glycan chains of lactoferrin, a protein present in bovine milk, although in this case no indications on the affinity of these bonds are given [ 142 ]. Finally, the body of evidence documenting the importance of glycan-glycan interactions for bacterial adhesion was recently extended by a study on the adhesion of Shigella to human lymphocytes [ 143 ]. Whereas Day and co-workers revealed the importance of glycan-glycan interactions in mediating binding of Shigella to host epithelial cells [ 139 ], this resent study by Belotserkovsky and co-workers provides evidence that glycan-glycan interactions are critical for Shigella pathogenesis by driving selective interactions with immune cells [ 143 ].…”
Section: Mechanisms Of Glycan-based Adhesion Of Bacteriamentioning
confidence: 99%
“…Finally, the body of evidence documenting the importance of glycan-glycan interactions for bacterial adhesion was recently extended by a study on the adhesion of Shigella to human lymphocytes [ 143 ]. Whereas Day and co-workers revealed the importance of glycan-glycan interactions in mediating binding of Shigella to host epithelial cells [ 139 ], this resent study by Belotserkovsky and co-workers provides evidence that glycan-glycan interactions are critical for Shigella pathogenesis by driving selective interactions with immune cells [ 143 ]. More precisely, they show that sialylated glycosphingolipids interact with the polysaccharide moiety of LPS, the major bacterial surface antigen, thus promoting Shigella binding to T cells.…”
Section: Mechanisms Of Glycan-based Adhesion Of Bacteriamentioning
confidence: 99%